2017
DOI: 10.1186/s12887-017-0919-4
|View full text |Cite
|
Sign up to set email alerts
|

Using LMS tables to determine waist circumference and waist-to-height ratios in Colombian children and adolescents: the FUPRECOL study

Abstract: BackgroundWaist circumference (WC) and waist-to-height ratio (WHtR) are often used as indices predictive of central obesity. The aims of this study were: 1) to obtain smoothed centile charts and LMS tables for WC and WHtR among Colombian children and adolescents; 2) to evaluate the utility of these parameters as predictors of overweight and obesity.MethodA cross-sectional study was conducted of a sample population of 7954 healthy Colombian schoolchildren [3460 boys and 4494 girls, mean age 12.8 (±2.3) years]. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
20
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 60 publications
(64 reference statements)
0
20
0
1
Order By: Relevance
“…Compared to reference populations from 1992 to 2015, overweight and obesity have increased by 17% and 9%, respectively [2]. High body weight and inadequate body fat distribution are associated with chronic diseases such as hypertension, cardiovascular disease, metabolic syndrome, and type 2 diabetes mellitus [3,4]. Physiologic changes caused by excess body fat include activation of the sympathetic nervous system and renin-angiotensin aldosterone system as well as endothelial dysfunction, which can lead to hypertension [5]; and increased insulin resistance, hypertriglyceridemia, decreased levels of high-density lipoprotein cholesterol, and changes in leptin levels and blood pressure are directly linked to a higher risk of cardiovascular disease [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared to reference populations from 1992 to 2015, overweight and obesity have increased by 17% and 9%, respectively [2]. High body weight and inadequate body fat distribution are associated with chronic diseases such as hypertension, cardiovascular disease, metabolic syndrome, and type 2 diabetes mellitus [3,4]. Physiologic changes caused by excess body fat include activation of the sympathetic nervous system and renin-angiotensin aldosterone system as well as endothelial dysfunction, which can lead to hypertension [5]; and increased insulin resistance, hypertriglyceridemia, decreased levels of high-density lipoprotein cholesterol, and changes in leptin levels and blood pressure are directly linked to a higher risk of cardiovascular disease [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps the rst step is to know how to evaluate these indicators. Body fatness and overweight have been widely studied using body mass index (BMI), which is body weight divided by the square of height (kg/m 2 ) [3,14]. However, a well-known disadvantage of BMI is that it does not differentiate between fat mass (FM) and fat-free mass (FFM), and does not take fat distribution into account [4,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Estudos descrevendo valores de percentis para CC têm apresentado resultados diferentes, uma vez que os valores de CC podem ser influenciados por idade, sexo e grupos étnicos, 9 - 11 dificultando o estabelecimento de valores de referência globais para essa medida antropométrica.…”
unclassified
“…Studies describing percentile values of WC have reported different results; WC measurements may be affected by age, sex and ethnicity, 9 - 11 which makes the establishment of global reference values difficult.…”
mentioning
confidence: 99%